Analisis Spasiotemporal Populasi Lalat Sciarid pada Budidaya Jamur Tiram - Rostaman Rostaman; Agus Dana Permana; Tati S. Subahar; Soelaksono Sastrodihardjo; Udjianna Pasaribu (Universitas Gadjah Mada, 2007)
Sciarid fly (Bradysia ocellaris Comstock) population growth and its distribution in the mushroom house was studied. Insects were collected using sticky yellow traps laid on 21 stations in the house over 18 weeks. At the first time, insects population was low. After that, insect population grew and reached at a maximum level in the 8th week. In subsequent weeks, insect population fluctuated. In the other hand, insect population dispersal also occured in the house. Based on spatiotemporal analysis using contour map and semivariogram analysis, insect population showed aggregation pattern, in a small group is called subpopulation. This was related to biological characters of insect such as eggs oviposition in mass and short flights.